Advanced control technique for substrate feed rate regulation of a feed batch fermentation - Rashid, Muhammad Mahbubur; Hizbullah, MD; Mohammad , Noor; Khan, M Jakir H (Academic journal Inc, 2012)
In this paper, an advanced control technique for substrate feed rate regulation of fed batch fermentation is developed. It is reliable in dealing with possible variations in the process condition. In this study, neural network and fuzzy logic methods are used in the design. As a case study, the baker’s yeast production process is chosen to test these controllers. The evaluation of the performance of the designed controllers is carried out through computer simulation. To obtain a reliable assessment, the results are then compared with those of the PI controller. The results have shown that the proposed approaches can be successfully applied to regulate of fed-batch fermentation to improve the operation of such processes.